How Well Do Accounting Education Organizations Prepare Professional Accountants for Green Concerns? - DIANNE FRISKO; DESI ARISANDI (The Indonesian Journal of Accounting Research, 2013)
This paper aims to capture a picture of the commitment of universities to the consideration of  sustainability development. As a part of it, this paper also tries to map the action taken by accounting education organizations (AEOs) through their programs, including curriculum development, learning method, research, and campus activities programs showing green concern in creating sustainable development. As a descriptive study, this paper used 50 universities on the top South-East Asia ranking web of world universities (Webometrics) in 2010. All data is taken from the information published on the web by each university as well as any other information that related to each university in the public domain. Based on the descriptive analysis, it is found that most AEOs lay out their green-concern on hardcore facilities rather than intrinsic development. Furthermore, as the recommendation in this paper, AEOs need to concentrate more on designing accounting curriculum, campus events and research that carry ethics and socio-environment considerations to respond to the ultimate demand and to balance the rapid change in various sectors. Finally, as a contribution to the future, it is hoped this paper will encourage AEOs, especially in Indonesia, to be more concerned and take more action with regard to the crucial purpose of creating sustainable development.